A study on Kolej Yayasan Sabah Students perseption on the existence of Yayasan Sabah - Maliau Basin conservation area / Sri Sudarmiyati Sainoh - Sainoh, Sri Sudarmiyati (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2005)
The MBCA is mostly montane heath forest and is a pristine wilderness with outstanding botanica riches. It is also an area with unique geological and hydrological features and it has an outstanding natural beauty with natural forests and many waterfalls as well as constituting one of the most importance headwaters of Sabah's largest river, Kinabatangan. Now talks are underway that the Maliau Basin may become Malaysia's third World Heritage Site. The objective of this study is to reveal the extent of KKYS (KYS)'s students awareness on the existence of Maliau Basin Conservation Area as an ecotourism and research centre.